2023
DOI: 10.1007/s15010-023-02094-9
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime-avibactam alone or in combination with Aztreonam versus Polymyxins in the management of carbapenem-Resistant Klebsiella pneumoniae nosocomial Infections (CAPRI study): a retrospective cohort study from South India

Racha Amarthya Sree,
Anand Gupta,
Nitin Gupta
et al.

Abstract: Introduction Carbapenem-resistant Klebsiella pneumoniae (CRKP) infections commonly cause hospital-acquired infections. The study aimed to compare the outcomes of CRKP infections between patients receiving ceftazidime avibactam +/− aztreonam and polymyxins in a hospital setting with a high prevalence of New Delhi Metallo Beta Lactamase production. Methods We conducted a retrospective cohort study from January 2020 to September 2022 in critically ill adult p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Four out of the analyzed patients died; three of them had a neoplastic disease, and one had a COVID-19 infection. This represents a lower mortality rate than in the Sree et al [16] (29.9%) analysis but higher than in the study by Zhang et al [19] (7.1%), although the latter analyzed hematologic patients.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Four out of the analyzed patients died; three of them had a neoplastic disease, and one had a COVID-19 infection. This represents a lower mortality rate than in the Sree et al [16] (29.9%) analysis but higher than in the study by Zhang et al [19] (7.1%), although the latter analyzed hematologic patients.…”
Section: Discussioncontrasting
confidence: 55%
“…Aztreonam is inactivated by ESBLs, KPC, and other cephalosporinases but remains stable against hydrolysis by MBLs. Thus, adding aztreonam to CZA enhances its activity by protecting aztreonam from the attack of ESBLs [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a mortality rate of 8-37.5% among patients treated by CAZ-AVI for CRKP. 8,[17][18][19][20] In this study, we report a 30-day mortality rate of 28.2%. The difference may be because of the patients' age, site of infection, and severity of disease.…”
Section: Discussionmentioning
confidence: 62%